Effectiveness of Socio-Constructive Collaboration Strategy on Post- Covid Primary School Children’s Learning Outcome in National Values (2024)
This study adopted socio-constructive collaboration strategy to enhance pupils’ learning outcome (social and cognitive skills) in national values after resumption from the compulsory closure of school for 6months. Quasi-experimental design was employed. Three hypotheses were raised and tested at 0.05 level of significance. 480 Primary one pupils from four public primary schools assigned to experimental and control within two local governments across four states participated in the study. The research spanned 15weeks. Validated instruments; Primary Pupils’ Achievement Test in National Values (PPATNV) and the Primary Pupils’ Social Skills Rating Scale (PPSSRC) were used to measure outcomes. Additionally, a Socio- constructive Pedagogical Instructional Guide (ScPIG) steered the delivery of the teaching and learning activities during the experiment. The study employed a statistical technique called analysis of covariance (ANCOVA) combined with a post-hoc test, especially the Bronfenbrenner test to analyse the pupils’ learning outcome. The results revealed significant positive effects of the intervention on both social skills and cognitive abilities (p<0.05) of pupils. Interestingly, school location also influences social skills. Furthermore, the intervention demonstrably improved students’ national values performance (p<0.05). The study concludes that a socio-constructivist collaborative teaching strategy significantly enhances pupils learning outcomes in areas related to social skills and cognitive development (national values comprehension). These findings suggest the potential benefits of adopting such strategies in primary school education for fostering well-rounded development in young learners